“Everything is so different...”: African students’ voices on the challenges of doing a PhD at a Portuguese university - Pinto, Susana (Journal of International Students, 2021)
In the scope of higher education internationalisation, Portuguese universities have been receiving an increasing number of students from Portuguese-Speaking countries, namely African countries, at the level of PhD studies. As highlighted in research, pursuing a PhD in an overseas context entails critical challenges for students, supervisors and higher education institutions. Against this background, this paper reports on the challenges faced by international African students attending a PhD programme in Education at a Portuguese university. Semi-structured interviews were conducted with seven students and results from thematic analysis show that the main challenges relate to language, integration into a different pedagogical/academic culture, adaptation to a different research culture, loneliness/homesickness and financial difficulties. Implications of findings for institutional policy and practice are put forward.